Security analysts and capital market anomalies - Guo, Li; Li, Frank Weikai; John Wei, K.C. (Journal of Financial Economics, 2020)
We examine the value and efficiency of analyst recommendations through the lens of capital market anomalies. We find that analysts do not fully use the information in anomaly signals when making recommendations. Analysts tend to give more favorable consensus recommendations to stocks classified as overvalued and, more important, these stocks subsequently tend to have particularly negative abnormal returns. Analysts whose recommendations are better aligned with anomaly signals are more skilled and elicit stronger recommendation announcement returns. Our findings suggest that analysts’ biased recommendations could be a source of market friction that impedes the efficient correction of mispricing.